Suitability mapping framework for solar photovoltaic pumps for smallholder farmers in sub-Saharan Africa - Schmitter, Petra S.; Kibret, K.S.; Lefore, Nicole; Barron, Jennie (Elsevier, 2018)
As solar panels become more a ordable, solar photovoltaic (PV) pumps have been identi ed as a high potential water lifting technology to meet the growing irrigation demand in sub-Saharan Africa (SSA). However, little is known aboutthegeo-spatial potentialofsolarbasedPVpumpingforirrigationtakinginto accountnotonlysolar radiation but also the availability of water resources and linkage to markets. This study developed a suitability framework using multi-criteria analysis in an open source GIS environment and tested it in the case of Ethiopia. Theaccessibilityofwaterresourceswasthedrivingfactorfordi erentscenarios.Suitabilityresultsfollowingthe groundwater scenarios showed good agreement with the available referenced well depth data. Comparing the suitability maps with available land use data showed that on average 9% (96103ha) of Ethiopian irrigated and 18% (3739103ha) of rainfed land would be suitable for solar PV pump irrigation. Furthermore, small solar PV pumps could be an alternative water lifting technology for 11% of the current and future small motorized fuel hydro-carbon pumps on smallholder farms (2166103ha). Depending on the technical pump capacity, between 155103ha and 204103ha of land would be suitable for solar PV pumps and provide smallholder farmers with the option to either pump from small reservoirs or shallow groundwater. With the ongoing interest in development for smallholder irrigation, the application of this model will help to upscale solar PV pumps for smallholder farmers in SSA as a climate smart technology in an integrated manner.